2019
DOI: 10.1371/journal.pone.0212003
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm applied to national surveillance data for the early detection of major dengue outbreaks in Cambodia

Abstract: Dengue is a national priority disease in Cambodia. The Cambodian National Dengue Surveillance System is based on passive surveillance of dengue-like inpatients reported by public hospitals and on a sentinel, pediatric hospital-based active surveillance system. This system works well to assess trends but the sensitivity of the early warning and time-lag to usefully inform hospitals can be improved. During The ECOnomic development, ECOsystem MOdifications, and emerging infectious diseases Risk Evaluation (ECOMOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…Of the 28 studies addressing EWS for dengue outbreaks, only 4 studies presented the user perspective on implementing EWS within national programs [ 12 , 21 , 26 , 27 ], and 24 studies showed EWS under development (i.e., model exercise); see Table 1 . Only 2 dengue studies used a prospective study design [ 28 , 29 ], and one applied both prospective and retrospective approaches [ 30 ]; the other 23 were retrospective analyses of surveillance data (1 of those specified as cohort study [ 21 ], 1 with a cross-sectional design [ 31 ], and 1 as a time series analysis [ 30 ]), and 2 studies were exclusively relying on mathematical simulation models [ 32 , 33 ]. The 2 Zika studies reported on exercises of testing EWS [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 28 studies addressing EWS for dengue outbreaks, only 4 studies presented the user perspective on implementing EWS within national programs [ 12 , 21 , 26 , 27 ], and 24 studies showed EWS under development (i.e., model exercise); see Table 1 . Only 2 dengue studies used a prospective study design [ 28 , 29 ], and one applied both prospective and retrospective approaches [ 30 ]; the other 23 were retrospective analyses of surveillance data (1 of those specified as cohort study [ 21 ], 1 with a cross-sectional design [ 31 ], and 1 as a time series analysis [ 30 ]), and 2 studies were exclusively relying on mathematical simulation models [ 32 , 33 ]. The 2 Zika studies reported on exercises of testing EWS [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…All 28 dengue studies relied on IBS, of which 24 studies were alarm informed, i.e., of outbreak predictive nature—using at least 1 meteorological, entomological or epidemiological indicator—and 4 studies [ 28 , 31 , 32 , 35 ] were case-informed EWS, i.e., of early outbreak detection—relying solely on previous trends of cases for outbreaks. Almost all studies demanded routine access to data as well as advanced statistical and analytical skills, but 5 studies [ 12 , 21 , 26 , 28 , 31 ] reported prediction tools that are adapted for less skilled users. The outbreak indicators used were hospitalized cases (2 studies) [ 12 , 21 ], laboratory-confirmed cases (23 studies), or suspected cases (3 studies) [ 12 , 28 , 31 ].…”
Section: Study Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that more than 3.9 billion people from 129 countries are at risk of contracting dengue fever, with one million deaths reported each year (Bhatt et al 2011;WHO 2020). The World Health Organization (WHO 2020) reported that the Asian region represents 70% of the global burden of dengue with several countries having become endemic including Cambodia (Ladien et al 2019), Indonesia (Maula et al 2018), Thailand (Srichan et al 2018), Singapore (Ong et al 2018), and Malaysia (Suppiah et al 2018).…”
Section: Introductionmentioning
confidence: 99%